2017
DOI: 10.1128/aem.00162-17
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sampling Method for Assessing Human-Pathogen Interactions in the Natural Environment Using Boot Socks and Citizen Scientists, with Application to Campylobacter Seasonality

Abstract: This paper introduces a novel method for sampling pathogens in natural environments. It uses fabric boot socks worn over walkers' shoes to allow the collection of composite samples over large areas. Wide-area sampling is better suited to studies focusing on human exposure to pathogens (e.g., recreational walking). This sampling method is implemented using a citizen science approach: groups of three walkers wearing boot socks undertook one of six routes, 40 times over 16 months in the North West (NW) and East A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…Thus, higher relative fitness of C. jejuni in the feces may suggest greater potential for preharvest colonization of turkey flocks with this species. As mentioned earlier, Campylobacter can spread within a turkey house directly via coprophagy or among different turkey houses and farms via vectors such as flies, equipment, and transport crates as well as via human traffic, e.g., through footwear, clothing, and vehicles (10,25,(31)(32)(33). During slaughter and processing, birds that became colonized with Campylobacter at the farm are more likely to lead to contamination of the carcasses with Campylobacter from the birds' intestinal contents (11,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, higher relative fitness of C. jejuni in the feces may suggest greater potential for preharvest colonization of turkey flocks with this species. As mentioned earlier, Campylobacter can spread within a turkey house directly via coprophagy or among different turkey houses and farms via vectors such as flies, equipment, and transport crates as well as via human traffic, e.g., through footwear, clothing, and vehicles (10,25,(31)(32)(33). During slaughter and processing, birds that became colonized with Campylobacter at the farm are more likely to lead to contamination of the carcasses with Campylobacter from the birds' intestinal contents (11,45).…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter's capacity to colonize chickens is enhanced upon passage through the birds' gastrointestinal (GI) tract and shedding in the fecal droppings (26)(27)(28)(29)(30). Campylobacter in the poultry feces can be then transmitted to other flocks and farms via insects, such as flies, and other vectors, including farm equipment and human traffic, with potential for downstream dispersal and contamination of the natural environment, e.g., surface water and soil (10,25,(31)(32)(33).…”
mentioning
confidence: 99%
“…However, our understanding of the reasons behind this are limited because unlike other bacteria Campylobacter does not multiple outside the gut. For example the response of Campylobacter cases to season and weather patterns has been attributed in the literature to several factors such as the cycling of the organisms in natural reservoirs and the seasonality of countryside visits exposing the public to Campylobacter in the environment [ 15 ]. Other authors have suggested the importance of seasonal and weather associated changes to food consumption (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been demonstrated to be just as, if not more, sensitive than the older drag swab method developed for use on chicken farms (Buhr et al 2007;Lungu et al 2012). Boot socks have also recently been used to sample for pathogens in the wider environment (Brena et al 2016;Jones et al 2017). The aim of this research was to analyse boot socks generated during the Enigma project for Campylobacter to determine the frequency with which STEC-associated virulence genes were detected in the English countryside (Jones et al 2017).…”
Section: Introductionmentioning
confidence: 99%